Prevalence of thyroid disorders during early pregnancy at Bharatpur Hospital, Chitwan district - Jha, Khusbu; Thakur, Chanda; Bhandari, Laxmi (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Introduction: Thyroid disorders are highly prevalent among pregnant women. Thyroid dysfunction, particularly during the first trimester, can significantly impact maternal and fetal outcomes, especially during the critical period of organogenesis, and thus adequate management is required. The rationale of this study is the necessity of adequate treatment of hypothyroidism during gestation, which minimizes the risks and generally makes it possible for pregnancies to be carried out to term without complications.Method: This is a cross-sectional observational study conducted from July 2020 to February 2021 at the Department of Obstetrics and Gynecology, Bharatpur Hospital, after ethical approval was taken from IRB NAMS (Ref no.529/2077/78). A total of 80 pregnant women in their first trimester (≤13 weeks) who met the inclusion criteria were recruited through convenience sampling. Thyroid function was assessed by measuring serum TSH, free thyroxine (FT4), and free triiodothyronine (FT3).Result: Among 80 pregnant women in the first trimester of pregnancy, 47(58.8%) were euthyroid, 2(2.5%) hyperthyroid,22 (27.5%) subclinical hypothyroid, and 9(11.3%) overt hypothyroid. Among them, 40.3% were multigravida women (30.4% and 13%, respectively) and 31.3% were primigravida (23.5% and 8.8%).Conclusion: Approximately one in four pregnant women had thyroid dysfunction, predominantly subclinical hypothyroidism. Given the substantial impact of thyroid disorders on maternal and fetal health, routine screening of pregnant women for thyroid disorders should be considered, especially in highprevalence settings like Nepal, to enable timely diagnosis and intervention.